Information System Quality Using Webqual 4.0 Method, Importance Performance Analysis (IPA) and Usability Testing - Gemara Adhiyasa Parahita Nurgraha; Gede Rasben Dantes; I Made Gede Sunarya (JST (Jurnal Sains dan Teknologi), 2026)
The Academic Information System (SIAKAD), as the primary digital service in higher education, has not fully met user expectations regarding ease of use, information quality, and service security. This study aims to analyze the suboptimal service quality of the SIAKAD website resulting from a gap between user expectations and system performance. The method used is a quantitative survey. The population in this study comprised all users of the Academic Information System (SIAKAD), including students, lecturers, and administrative staff. The sampling technique was carried out in two stages: purposive sampling and accidental sampling. The number of respondents in this study was 65 for the WebQual 4.0 and IPA analyses, and 20 for usability testing. Data collection methods in this study were closed questionnaires, interviews, observations, and usability testing. The research instrument used a questionnaire. The analysis assessed the dimensions of usability, information quality, and service interaction quality and mapped the level of importance and performance to determine improvement priorities. The results showed that all aspects of SIAKAD were highly important, but the actual quality fell short of user expectations. The system performed well in display clarity, information relevance, and academic communication, but was less than optimal in information updates, data security, and user experience. IPA prioritizes user experience, information accuracy, data security, and communication effectiveness for improvement. Usability testing showed that the system effectively supports academic functions but remains inefficient and not yet fully satisfying to users.